Faces of the Frontier - Marschall, Thomas; Braunshor, Nikolaus (Austria : NonPlus Filmproduction, 2009)
The State of Mato Grosso (“the luxuriant forest”) is Brazil’s biggest exporter of agricultural produce. Main products exported are soy for rearing livestock and cotton for the clothing industry. Big landowners in possession of large areas of land and agro-companies lay claim to progress and the future. In the service of an agro-industry now supplying world markets, they are slowly eradicating every other form of work and production in the region. Settlers, smallholders and squatters are nonetheless defying the laws of the market in an attempt to retain land and economic independence. Between these two fronts, bewildered by the consequences of the “white man’s” economic policy, stands Brazil’s indigenous population. Forced into reservations or driven from their land, these people have become mute witnesses to the destruction of their home and culture. Global capitalism is making unstoppable inroads into what was not long ago Brazil’s Virgin hinterland. The rule of law is still far away. In this part of Brazil club law prevails and many who dream of land and a home pay for it with their lives.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films